Improvement of electrical synchrony in cardiac resynchronization therapy using dynamic atrioventricular delay programming and multipoint pacing. Issue 12 (21st October 2021) - Schiedat, Fabian; Mijic, Dejan; Karosiene, Zana; Bogossian, Harilaos; Zarse, Markus; Lemke, Bernd; Hanefeld, Christoph; Mügge, Andreas; Kloppe, Axel
Abstract: Background: Optimization of cardiac resynchronization therapy (CRT) is often time‐consuming and therefore underused in a clinical setting. Novel device‐based algorithms aiming to simplify optimization include a dynamic atrioventricular delay (AVD) algorithm (SyncAV, Abbott) and multipoint pacing (MPP, Abbott). This study examines the acute effect of SyncAV and MPP on electrical synchrony in patients with newly and chronically implanted CRT devices. Methods: Patients with SyncAV and MPP enabled devices were prospectively enrolled during implant or scheduled follow‐up. Blinded 12‐lead electrocardiographic acute measurements of QRS duration (QRSd) were performed for intrinsic QRSd (Intrinsic), bi‐ventricular pacing (BiV), MPP, BiV with SyncAV at default offset 50 ms (BiVSyncAVdef ), BiV with SyncAV at patient‐specific optimised offset (BiVSyncAVopt ), MPP with SyncAV at default offset 50 ms (MPPSyncAVdef ), and MPP with SyncAV at patient‐specific optimised offset (MPPSyncAVopt ). Results: Thirty‐three patients were enrolled. QRSd for Intrinsic, BiV, MPP, BiVSyncAVdef, BiVSyncAVopt, MPPSyncAVdef, MPPSyncAVopt were 160.4 ± 20.6 ms, 141.0 ± 20.5 ms, 130.2 ± 17.2 ms, 121.7 ± 20.9 ms, 117.0 ± 19.0 ms, 121.2 ± 17.1 ms, 108.7 ± 16.5 ms respectively. MPPSyncAVopt led to greatest reduction of QRSd relative to Intrinsic (−31.6 ± 11.1%; p < .001), showed significantly shorter QRSd compared to all other pacing configurations ( p < .001) and shortest QRSd in every patient. Shortening of QRSd was not significantly different between newly and chronically implanted devices (−51.6 ± 14.7 ms vs. −52.7 ± 21.9 ms; p = .99). Conclusion: SyncAV and MPP improved acute electrical synchrony in CRT. Combining both technologies with patient‐specific optimization resulted in greatest improvement, regardless of time since implantation. Whats new Novel device‐based algorithms like a dynamic AVD algorithm (SyncAV, Abbott) and multipoint pacing (MPP, Abbott) aim to simplify CRT optimization. Our data show that a combination of patient tailored SyncAV optimization and MPP results in greatest improvement of electrical synchrony in CRT measured by QRS duration, regardless if programmed in newly or chronically implanted devices. This is the first study to our knowledge to examine a combination of these device‐based algorithms. The results help understanding the ideal ventricular excitation in heart failure.